Considérations sur la faillite et l’assurance-vie - Langlois, André (Assurances)

(untitled) (HEC Montréal, 1981)
With the tightness of business, the number of bankruptcies is increasing from month to month. The author studies here the case of life insurance covering the dead bankrupt. Is the insurance included in the available funds payable to the creditors or can it be considered as a shelter for the bona fide beneficiary and particularly if he is a member of the insured's family?